New Immunocapture Enzyme (ICE) Assay for Quantification of Cancer Procoagulant Activity: Studies of Inhibitors - Mielicki, Wojciech P; Tagawa, Maureen; Gordon, Stuart G (Thrombosis and Haemostasis, 1994)
A new, sensitive and specific immunocapture enzyme (ICE) assay for quantitation of the enzymatic activity of cancer procoagulant (CP) has been developed. The assay had good reproducibility (inter- and intra-assay CV were 6.4% and 5.7% respectively) and was linear for concentrations of CP from 0.5 μg/ml to 10 μg/ml (r2 = 0.995). Using this assay the inhibition of CP by iodoacetamide, mercuric chloride, E-64, leupcptin and antipain was demonstrated. There was no significant effect of cystatin and natural plasma proteinase inhibitors α1-antitrypsin, α1-antichymotrypsin, α2-macroglobulin and antithrombin-III/heparin, on the activity of the CP.